2002
DOI: 10.1128/iai.70.9.4968-4976.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Regulator PerR Is Involved in Oxidative Stress Response and Iron Homeostasis and Is Necessary for Full Virulence of Streptococcus pyogenes

Abstract: Ferric uptake regulator (Fur) and Fur-like proteins form an important family of transcriptional regulators in many bacterial species. In this work we have characterized a Fur-like protein, the peroxide regulator PerR, in an M1 serotype of Streptococcus pyogenes. To determine the role of PerR in S. pyogenes, we inactivated the gene by allelic replacement. PerR-deficient bacteria showed 48% reduction of 55 Fe incorporation from the culture medium. Transcriptional analysis revealed that mtsA, encoding a metal-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
117
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 59 publications
12
117
1
Order By: Relevance
“…1C). This confirmed that the virulence of the perR deficient mutant was attenuated in the animal model in accordance with previous reports (12)(13)(14). To summarize, these data demonstrated that the perR deficient mutant is useful for discovery of PerR-regulated virulence factors in S. pyogenes.…”
Section: Validation Of Characteristics Of the Perr Deficient Mutant-supporting
confidence: 79%
See 3 more Smart Citations
“…1C). This confirmed that the virulence of the perR deficient mutant was attenuated in the animal model in accordance with previous reports (12)(13)(14). To summarize, these data demonstrated that the perR deficient mutant is useful for discovery of PerR-regulated virulence factors in S. pyogenes.…”
Section: Validation Of Characteristics Of the Perr Deficient Mutant-supporting
confidence: 79%
“…After this computational prediction, we hypothesize a novel role for PerR in regulating protein secretion in S. pyogenes. In previous investigations, the PerR regulator was shown to be involved in oxidative stress responses and virulence, and there was no evidence to show that PerR is involved in protein secretion (12)(13)(14). In the present study, we discovered 13 PerR-regulated secreted proteins, which demonstrates that PerR can control the protein secretion directly or indirectly to influence the virulence of S. pyogenes.…”
Section: Validation Of Characteristics Of the Perr Deficient Mutant-supporting
confidence: 47%
See 2 more Smart Citations
“…By differential gene expression, GAS successfully transitions through three stages of host infection: namely, 1) establishment of infection, 2) adaptation, and 3) dissemination ( Figure 6). Information about stage 1 is based on an expanding body of work, 8,10,11,34,103 and our results support this information by combined early expression of Mga, Ihk/Irr, and FasBCA/X regulatory systems that promote evasion of immune and innate host defenses and enhance host cell contact through surface adhesin production. Down-regulation of the negative regulatory systems of PerR, CovR/S, and CrgR promote production of reactive oxygen species detoxifying enzymes, hyaluronic acid capsule, and antimicrobial peptide resistance mechanisms, respectively, 8,35,[103][104][105][106][107] and our soft tissue model demonstrates similar results.…”
Section: Emerging Model Of Gas Gene Regulation In Vivosupporting
confidence: 69%